Analysis Effectiveness of the Online Learning through the Use of Google Classroom during the COVID-19 Pandemic - Putri Novira; Albinus Silalahi; Saronom Silaban (Universitas Lampung, 2021)
The purpose of this study was to analyze the effectiveness of online learning asynchronously through the use of google classroom media at Medan State University, Chemistry Education Departement, batch 2018 in the chemical separation course during the COVID-19 pandemic. This study used descriptive qualitative method. The sample of this research was 29 students of the fifth semester class A chemistry education study program in 2018. The data collection technique used was filling out a questionnaire via google form as many as 24 statements. The results obtained indicate that the benefits of google classroom are good with a percentage of 76.9%, ease, quality of user use, use of google classroom and effectiveness are 86.3%, 80.3%, 81.9%, and success respectively. 88.6% in very good category. In general, the effectiveness of online learning through the use of google classrooms at Medan State University, Chemistry Education Study Program class of 2018 is very good, students find it easy to use google classroom, have very good quality of use of learning, and have good enough use for students.Keywords: online learning, COVID-19, google classroom, effectiveness.